HUBUNGAN KOMPETENSI PROFESIONAL DENGAN KINERJA TUTOR DI UPTD SPNF SKB UJUNG PANDANG KOTA MAKASSAR - Latang Latang; Rudi Amir; Untung Untung (UNIVERSITAS NEGERI MAKASSAR, 2024)
The Relationship between Professional Competence and Tutor Performance at UPTD SPNF SKB Ujung Pandang Makassar City. The aim of this research is to determine the relationship between professional competence and tutor performance at UPTD SPNF SKB Ujung Pandang Makassar City. This type of research is ex post facto research. The population in this study was all students who took part in learning in non-formal education units totaling 60 people. Data collection was carried out by distributing questionnaires and documentation. The data collected in the research was analyzed using descriptive statistical techniques and inferential statistics. Based on the results of data analysis, with 60 respondents filling out the professional competency questionnaire for heads of educational institutions and teacher competency, there was a correlation of 0.713 from the t table of 0.514. Thus, t count > t table, the correlation coefficient level which is between 0.70-0.80 is considered high. This shows that the data analysis value is higher than the r table value, so the proposed research hypothesis is accepted. Based on the research results, there is a relationship between professional competence and tutor performance at UPTD SPNF SKB Ujung Pandang Makassar City